Towards a conceptual description of Physical and Rehabilitation Medicine - Gutenbrunner, Christoph; Meyer, Thorsten; Melvin, John; Stucki, Gerold (Journal of rehabilitation medicine, 2011)
Physical and Rehabilitation Medicine (PRM) is an independent medical specialty focusing on the improvement of functioning. A shared understanding of concepts is of vital importance for integrated action in this field. The aim of the present paper is to provide a conceptual model of PRM, to give background on its development and adoptions, and to explain the choice of terms, phrases, and concepts. It is based on the terms and concepts of the International Classification of Functioning, Disability and Health (ICF) that provides a widely accepted conceptual model and taxonomy of human functioning. Based on the White Book on Physical and Rehabilitation Medicine in Europe of 2006 a first proposal for a conceptual description of rehabilitation has been published in 2007. This proposal has been subjected to comments for modifications and amendments. E.g. it was underlined that PRM can apply both a health condition perspective including curative approaches and measures aiming at body functions and structures and a multi-dimensional and multi-professional team approach aiming to optimize functioning from a comprehensive functioning and disability perspective. The interaction between the PRM specialist and the person should be characterized as a partnership. PRM specialists work across all areas of health services and across all age groups. In summary, the specialty of PRM is characterized as the medicine of functioning.